Hubungan Pengetahuan Wanita Pekerja Seksual Tentang Infeksi Menular Seksual Dengan Keteraturan Pemeriksaan Infeksi Menular Seksual - Ni Putu Witha Rahayuni; Ni Gusti Kompiang Sriasih; I Gusti Ayu Surati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2019)
In Indonesia, the cases of leucorea in 2016 is 10.672 cases and ulcus genital is 1.628 cases, where Female Sex Workers (FSWs) is a second group that have high risk with Sexual Transmitted Infections (STI). This study aim to know the relationship between knowledge of Female Sex Workers about STI with compliance of STI testing in Denpasar Selatan II Primary Health Centre. This study was using analytic corelational with crossectional approach. Total sample that used are 43 respondents with inclusion and exclusion criteria. The sampling method was non probability sampling with purposive sampling. The respondent’s data was collected by questionnaire and took place in Denpasar Selatan II Primary Health Centre and spent one month to finish, on May 2018. The data analytic method was bivariate analytic with Chi Square test. The result showed that 60% respondents had a good knowledge about STI and only 42% respondents did STI testing routinly. Knowledge of  FSWs about STI and compliance in doing STI testing does not have a significant relationship (p0,05). Based on that result, it is important to provide education about the importance of doing STI testing routinly and efforts to increase the FSWs awareness, so it can prevent the STI.Keywords: Knowledge; Compliance; STI Testing; Female Sex Workers